2001
DOI: 10.1002/jat.796
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lead and zinc on rat male reproduction at ‘biochemical and histopathological levels’

Abstract: Sequential lead accumulation and biochemical and histopathological changes were observed in rat testis and epididymis after oral administration at varied doses of lead (10, 50 and 200 mg kg(-1) body wt.) for 3 months and also following the concomitant administration of lead with zinc (1 mg kg(-1) body wt. +50 mg Pb kg(-1) body wt.). Accumulation of lead in both testis and epididymis increased with dose. The concomitant administration of zinc reduced the lead levels. Similarly, dose-related changes were seen in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 27 publications
4
55
0
2
Order By: Relevance
“…These data suggested that Pb increased abnormal sperm and Zn could decrease it. This agrees with the observation by Batra et al 19,22) . That the toxic effects of Pb on male reproductive system could be ameliorated by Zn supplementation.…”
Section: Discussionsupporting
confidence: 94%
“…These data suggested that Pb increased abnormal sperm and Zn could decrease it. This agrees with the observation by Batra et al 19,22) . That the toxic effects of Pb on male reproductive system could be ameliorated by Zn supplementation.…”
Section: Discussionsupporting
confidence: 94%
“…Also the interstitial spaces were abnormally widened and the Leydig cells were not observable, hence destroyed; this revealed the antifertility action of lead oxide [11]. Photomicrograph of the testis of animal in group treated with both extract of Enantia chlorantha and lead (IV) oxide, shows degenerating of the seminiferous epithelium.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies on reproductive system of animals have reported lead as a toxic substance for testicular tissue and functions (29), including spermatogenesis and mature sperm formation (30).It was suggested that spermatogenesis regression is caused by increased inhibin B synthesis in highly lead exposed subjects (31). Many studies agree with this finding (32,33,34,35)including a study which was done on mice and found that there is a significant decrease in the number of spermatozoa within the epididymis in mice exposed to lead acetate in drinking water (36), and prevent spermatogenesis in rats (37). On the other hand some researchers have failed to demonstrate such a correlation between lead and sperm count (38,39).…”
Section: Discussionmentioning
confidence: 99%